Analysis of the Wing Tsun Punching Methods - Jeff Webb (Universidad de León, 2012)
The three punching techniques of Wing Tsun, while few in number, represent an effective approach to striking with the closed fist. At first glance, the rather short stroke of each punch would seem disproportionate to the amount of power it generates. Therefore, this article will discuss the structure and body mechanics of each punch, in addition to the various training methods employed for developing power. Two of the Wing Tsun punches, namely the lifting punch and the hooking punch, are often confused with similar punches found in Western boxing. The key differences between the Wing Tsun and boxing punches, both in form and function, will be discussed. Finally, the strategy for applying the Wing Tsun punches will serve as the greatest factor in differentiating them from the punches of other martial arts styles.